2023
DOI: 10.1186/s12889-023-15983-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities and concentration of the spread of the COVID-19 pandemic in the province of Quebec, Canada

Abstract: Background Recent studies suggest that the risk of SARS-CoV-2 infection may be greater in more densely populated areas and in cities with a higher proportion of persons who are poor, immigrant, or essential workers. This study examines spatial inequalities in SARS-CoV-2 exposure in a health region of the province of Quebec in Canada. Methods The study was conducted on the 1206 Canadian census dissemination areas in the Capitale-Nationale region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Regarding neighbourhood characteristics, material deprivation was positively associated with anti-N seropositivity, while social deprivation was negatively associated. This may be because essential workers who cannot work remotely are more likely to live in materially deprived neighbourhoods, 28 and socially deprived neighbourhoods are protected by smaller household sizes. Interestingly, the association between seropositivity and high material deprivation lessened during the more recent Omicron wave, while the association with low social deprivation persisted.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding neighbourhood characteristics, material deprivation was positively associated with anti-N seropositivity, while social deprivation was negatively associated. This may be because essential workers who cannot work remotely are more likely to live in materially deprived neighbourhoods, 28 and socially deprived neighbourhoods are protected by smaller household sizes. Interestingly, the association between seropositivity and high material deprivation lessened during the more recent Omicron wave, while the association with low social deprivation persisted.…”
Section: Discussionmentioning
confidence: 99%
“…across different demographic groups [25][26][27] , we found that combined seroprevalence differed by age, geographic area and district-level socio-economic deprivation, while infection and basic immunization differed by age and geographic area. The still relatively low infection rate recorded in the overall population is most probably due to the fact that the majority of our data were collected just before the more transmissible Omicron variant became dominant over the Delta variant 28 .…”
Section: Consistent With Previous Findings Showing Disparities In Bot...mentioning
confidence: 99%